The Campsicnemus lobatus and zigzag groups in the Society Islands, French Polynesia (Diptera: Dolichopodidae) - Evenhuis, Neal L. (Zootaxa, 2008)
The genus Campsicnemus is recorded for the first time from the Society Islands in French Polynesia. Two endemic species groups are recognized: the lobatus group (5 new species) and the zigzag group (5 new species) and keys given to species within them. The following 10 new species are described and illustrated: Campsicnemus borabora Evenhuis, n. sp. (Bora Bora); C. lobatus Evenhuis, n. sp. (Moorea); C. mylloseta Evenhuis, n. sp. (Huahine); C. ogradyi Evenhuis, n. sp. (Tahiti); C. ostlinx Evenhuis, n. sp. (Raiatea); C. paralobatus Evenhuis, n. sp. (Tahiti); C. rheocrenus Evenhuis, n. sp. (Tahiti); C. tahaanus Evenhuis, n. sp. (Tahaa); C. tunoa Evenhuis, n. sp. (Moorea); and C. zigzag Evenhuis, n. sp. (Tahiti).